PREDICTORS OF FAMILY ACCOMMODATION IN OBSESSIVE COMPULSIVE DISORDER IN INDIAN POPULATION - Kshirsagar, Sharad; Dinesh Tembe; Mangot, Ajish (International Journal of Psychosocial Rehabilitation, 2020)
In adults its estimated prevalence of approximately 1%–3% has been observed. The course of the OCD may be determined by the familial involvement. Family accommodation (FA) refers to the ability of how family members assist in compulsive rituals, modify their routines, provide reassurance to avoid the distress experienced by a patient suffering from OCD. The previous studies on FA were conducted in pediatric OCD where they found that 70% of parents were involved with their child’s symptoms in some way. Inclusion criteria for Group 1 (obsessive–compulsive disorder patients) involves patients who meets DSM-5 criteria of OCD, with Yale–Brown Obsessive Compulsive Scale (YBOCS) score >8 1, duration of illness more than a year ,Age 20–61 years , Hamilton Rating Scale for Depression (HAM-D) score≤14 , No other Axis I psychiatric disorder ascertained by Mini International Neuropsychiatric Interview Version 6 (MINI 6.0) The sociodemographic profile of the patients, as well as caregivers, is shown in Table 1. There was a slight preponderance of females (53.2%), and the majority of the sample was married (62.3%). Majority of the caregivers were spouses (60.2%) of the patients, followed by parents (31.4%). The clinical profile of the OCD patients is shown in Table 2 The mean duration of illness was 5.24 years, and the mean age of onset 9.71 years. Our study adds useful information to the existing Indian research, that reveals, FA is a common phenomenon in caregivers of patients with OCD. It is particularly frequent when the patient has prominent contamination symptoms. So, clinicians should be aware of its high probability, and future research should be performed toward the development of family-based psychotherapeutic interventions, which may prove beneficial for these families